2022
DOI: 10.3389/fmicb.2022.1039217
|View full text |Cite
|
Sign up to set email alerts
|

Glucogenic and lipogenic diets affect in vitro ruminal microbiota and metabolites differently

Abstract: This study was conducted to evaluate the effects of two glucogenic diets (C: ground corn and corn silage; S: steam-flaked corn and corn silage) and a lipogenic diet (L: sugar beet pulp and alfalfa silage) on the ruminal bacterial and archaeal structures, the metabolomic products, and gas production after 48 h in vitro fermentation with rumen fluid of dairy cows. Compared to the C and S diets, the L dietary treatment leaded to a lower dry matter digestibility (DMD), lower propionate production and ammonia-nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
0
1
1
Order By: Relevance
“…As previously mentioned, diet is known to greatly affect the composition and activity of the ruminal microbiota. Although changes in the ruminal microbiota can partly explain the results obtained in our study, Jami and Mizrahi (57) reported that differences in ruminal bacterial populations among animals fed the same diet were substantially higher than those promoted by different diets. Moreover, the authors concluded that despite the variation in bacterial taxa among animals, the microbiota was phylogenetically highly similar (82%) and thus did not affect fermentation ability.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…As previously mentioned, diet is known to greatly affect the composition and activity of the ruminal microbiota. Although changes in the ruminal microbiota can partly explain the results obtained in our study, Jami and Mizrahi (57) reported that differences in ruminal bacterial populations among animals fed the same diet were substantially higher than those promoted by different diets. Moreover, the authors concluded that despite the variation in bacterial taxa among animals, the microbiota was phylogenetically highly similar (82%) and thus did not affect fermentation ability.…”
Section: Discussioncontrasting
confidence: 56%
“…Moreover, the authors concluded that despite the variation in bacterial taxa among animals, the microbiota was phylogenetically highly similar (82%) and thus did not affect fermentation ability. Hua et al ( 58 ) compared the effects of glucogenic and lipogenic diets on ruminal bacterial community structure, fermentation intermediary metabolites, and methane production following 48 h of incubation with a ruminal inoculum. Although several amylolytic and cellulolytic bacteria were found to be sensitive to dietary differences, most highly abundant bacteria were stable or were only marginally affected, thus highlighting the relevance of the microbiota profile of ruminal inocula in short-term in vitro fermentation studies.…”
Section: Discussionmentioning
confidence: 99%